Training and Development as a Strategic Pillar of Human Resource Development: Integration, Impact, and Innovation in Modern Organizations - Yulianto Surya Adhi (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Rapid technological change, growing skill obsolescence, and increasing organizational complexity have intensified the strategic importance of Training and Development within Human Resource Development. Despite sustained investment in employee learning, many organizations continue to struggle with translating training initiatives into sustained performance improvement and organizational adaptability. This study addresses this challenge by examining Training and Development as a strategic pillar embedded within an integrated HRD system rather than as an isolated organizational function. The study aims to analyze how Training and Development is implemented, integrated with other HRD components, and transformed through innovation, as well as how it contributes to organizational performance and capability development. This research adopts a qualitative and integrative design based on systematic analysis of recent peer reviewed literature and illustrative organizational evidence drawn from contemporary organizational reports. Data were analyzed thematically to identify recurring patterns related to strategic alignment, system integration, learning transfer, and innovation in Training and Development practices. The findings indicate that Training and Development deliver meaningful organizational value when strategically aligned with future capability needs, integrated with performance management and HR automation, and supported by employee engagement mechanisms. Digital learning infrastructure enhances accessibility and relevance, but its effectiveness depends on managerial capability and data informed decision making. Persistent challenges remain in learning transfer and impact measurement, although emerging technologies show potential to address these limitations. The study contributes to HRD theory by conceptualizing Training and Development as a dynamic organizational capability. Practically, it offers guidance for designing integrated and future oriented development systems that support long term organizational resilience.